Marine Biodiversity Records - Mieszkowska, Nova
Marine Biodiversity Records is a rapid peer-reviewed, online, open access publication that complements the long-established Journal of the Marine Biological Association of the United Kingdom. Marine Biodiversity Records has been launched in response to the changing marine and coastal environment and an increasing demand for the documentation of marine organisms in locations where they have not formerly been recorded, as well as of species loss from habitats. Marine Biodiversity Records therefore welcomes original research articles which document and review changes in geographical ranges of marine species, including the effects of the introduction of novel or alien species to marine ecosystems, and of taxonomic studies relevant to these changes. Marine Biodiversity Records is one of the official journals of The Marine Biological Association of the United Kingdom, a world-leading marine biological society, which has a mission to promote scientific research into all aspects of life in the sea and to disseminate to the public the knowledge gained.